Quantifying the Effect of Weather on Advanced Air Mobility Operations - Ashima Sharma; Jay Patrikar; Brady Moon; Sebastian Scherer; Constantine Samaras (Findings)
We quantify and analyze the potential number of flyable hours for an advanced air mobility (AAM) vehicle over the contiguous United States. We use Meteorological Aerodrome Reports (METARs) from 2019, covering 91 airports in the US. By filtering the METARs based on Federal Aviation Administration mandated flight conditions and the vehicle’s physical capabilities, our analysis shows nearly double the amount of annual acceptable flying time between the most flyable and least flyable locations in the country and identifies the largest cause of non-flyable hours as cloud cover. Our work can be used to understand the viability of AAM vehicles in a geographic location.